The interval of rescue treatment does not affect the efficacy and safety of Helicobacter pylori eradication: A prospective multicenter observational study - Minjuan Lin; Junnan Hu; Jing Liu; Juan Wang; Zhongxue Han; Xiaohong Wang; Zhenzhen Zhai; Yanan Yu; Wenjie Yuan; Wen Zhang; Zhi Wang; Qingzhou Kong; et al. (Chinese Medical Journal)
Abstract. Background:. The effect of the interval between previous Helicobacter pylori (H. pylori) eradication and rescue treatment on therapeutic outcomes remains unknown. The aim of this study was to investigate the association between eradication rates and treatment interval durations in H. pylori infections. Methods:. This prospective observational study was conducted from December 2021 to February 2023 at six tertiary hospitals in Shandong, China. We recruited patients who were positive for H. pylori infection and required rescue treatment. Demographic information, previous times of eradication therapy, last eradication therapy date, and history of antibiotic use data were collected. The patients were divided into four groups based on the rescue treatment interval length: Group A, ≥4 weeks and ≤3 months; Group B, >3 and ≤6 months; Group C, >6 and ≤12 months; and Group D, >12 months. The primary outcome was the eradication rate of H. pylori. Drug compliance and adverse events (AEs) were also assessed. Pearson’s χ2 test or Fisher’s exact test was used to compare eradication rates between groups. Results:. A total of 670 patients were enrolled in this study. The intention-to-treat (ITT) eradication rates were 88.3% (158/179) in Group A, 89.6% (120/134) in Group B, 89.1% (123/138) in Group C, and 87.7% (192/219) in Group D. The per-protocol (PP) eradication rates were 92.9% (156/168) in Group A, 94.5% (120/127) in Group B, 94.5% (121/128) in Group C, and 93.6% (190/203) in Group D. There was no statistically significant difference in the eradication rates between groups in either the ITT (P = 0.949) or PP analysis (P = 0.921). No significant differences were observed in the incidence of AEs (P = 0.934) or drug compliance (P = 0.849) between groups. Conclusion:. The interval duration of rescue treatment had no significant effect on H. pylori eradication rates or the incidence of AEs. Registration:. ClinicalTrials.gov, NCT05173493.